The Effect of Price and Product Quality on Purchasing Decisions for Ms Glow Products at Che Ms Glow Country in Jembrana District - Ni Made Ayu Apriliana; I Dewa Ayu Tita Permata Tabita; I Gusti Agung Sasih Gayatri (Digital Innovation : International Journal of Management, 2024)
The problems raised in this study are whether price (X1) affects purchasing decisions (Y), whether product quality (X2) affects purchasing decisions (Y) and whether price (X1) and product quality (X2) affect purchasing decisions (Y). The sample in this study amounted to 30 people. The data analysis techniques used in this study are validity and reliability tests, classical assumptions, multiple linear regression tests, determination tests (adjusted R2), t tests and F tests. The analysis results show the regression model Y = 1.155 + 0.421 (X1) + 0.186 (X2). The conclusion obtained is that price (X1) has a positive and significant effect on purchasing decisions (Y) for Ms Glow products at Che Ms Glow Negara in Jembrana, which is indicated by the regression coefficient b1X1 which is positive. Product quality (X2) has a positive and significant effect on purchasing decisions (Y) of Ms Glow products at Che Ms Glow Negara in Jembrana, which is indicated by the regression coefficient b2X2 which is positive. The magnitude of the effect of price and product quality on purchasing decisions for Ms Glow products at Che Ms Glow Negara in Jembrana is 0.063 or 63%, while 37% is influenced by other factors not examined. The independent variable that has a dominant influence on purchasing decisions (Y) can be seen from the results of the Standardised Coefficients Beta value is the price variable (X1) which is 0.161 while the product quality variable (X2) is 0.360.